Negative Implications of Public Private Partnership at the Port of Rembang Sluke Terminal - Dwi Yoga Ambal Ariski; Tri Yuniningsih; Augustin Rina Herawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of infrastructure development in the Rembang Regency area is oriented towards the Rembang Port, the Sluke Terminal. The use of the concept of Public private partnership which was carried out to carry out port development found various problems ranging from management and disputes over land reclamation between the private sector and local governments. The occurrence of this problem shows the local government's lack of readiness to regulate public policy, so there is a need for a problem analysis to solve the problem. Bardach's theory is the basis for analytical theory in solving this problem, covering aspects of technical feasibility, economic and financial aspects, political aspects and organizational aspects of implementing policy evaluation measurements based on authority, institutional commitment, capability, and organizational support. The research method used is a qualitative descriptive method with analytical techniques using Bardach's theory and Rembang district regulations. The results show that the negative implications of PPP (Public Private Partnership) in the process of managing the Port of Rembang at Sluke Terminal are that there are still HGB land disputes over HPL between the private sector and the Rembang district government, a lot of intervention from the political elite in this problem and the emergence of state losses (government Rembang Regency) due to land disputes and port management, lack of adequate human resources to implement the concept of public private partnership with private parties. Recommendations: local governments need to study the legality of cooperation agreements, seek legal steps to be taken immediately, there is communication between political elites, regional heads are expected to be able to make regulations that lead to dispute resolution.